Hotel website quality, perceived flow, customer satisfaction and purchase intention - Ali, Faizan (Journal of hospitality and tourism technology, 2016)
Purpose This study aims to examine the relationships between hotel website quality, perceived flow, customer satisfaction and purchase intentions. Furthermore, this study also examines if perceived flow mediates the relationships between hotel website quality, customer satisfaction and purchase intentions. Design/methodology/approach The stimulus-organism-response framework is used as the theoretical framework for this study. A total of 441 valid online questionnaires were collected to empirically test the measurement and structural model using partial least square path modeling approach. The study sample includes hotel guests who booked their hotels via online travel agencies and/or hotel websites. Findings The findings confirm that hotel website quality influences customers’ perceived flow, which in turn, influences their satisfaction and purchase intention. Moreover, perceived flow also mediates the relationships between hotel website quality, customer satisfaction and purchase intentions. Originality/value Hotel website quality, perceived flow, customer satisfaction and purchase intentions altogether are not well understood in current literature despite the important implication for managers, academicians and consumers alike. This study contributes to the field of e-commerce marketing, retailing and e-tourism research.